Experiences of receiving an mHealth application with proactive nursing support among community-dwelling older adults: a mixed-methods study - Arkers Kwan Ching Wong; Jonathan Bayuo; Frances Kam Yuet Wong; Karen Kit Sum Chow; Siu Man Wong; Bonnie Bo Wong; Khloe Hau Yi Law (BMC, 2024)
Abstract Background As the population ages, a plethora of digital and mobile health applications for assistance with independent living have emerged. Still unknown, however, is how older adults sustain the use of these applications. Aim This study sought to explore the experiences of older adults following their participation in a programme that combined the use of an mHealth application with proactive telecare nursing support. Methods We employed a concurrent mixed-methods design for this study. The quantitative strand included a survey, whereas the qualitative strand included open-ended questions as part of the survey to understand the participants' experiences. Participants for this study were community-dwelling older adults who had taken part in an interventional study that sought to examine the effects of mHealth and nurse support. A convenience sampling approach was employed to recruit potential participants for this study. Findings : Fifty-five older adults participated. The majority expressed positive attitudes and satisfaction with the app and the nurses' support. The app and nurses' support helped participants to understand their health status and obtain health information. Reasons to halt app usage included technical issues and limited social support. Conclusion Mobile apps with professional follow-up support could potentially support older adults in the community, although emerging concerns need to be addressed to sustain long-term usage of these apps.